2018
DOI: 10.1021/acs.analchem.8b02479
|View full text |Cite
|
Sign up to set email alerts
|

Crowd on a Chip: Label-Free Human Monoclonal Antibody Arrays for Serotyping Influenza

Abstract: Rapid changes in influenza A virus (IAV) antigenicity create challenges in surveillance, disease diagnosis, and vaccine development. Further, serological methods for studying antigenic properties of influenza viruses often rely on animal models and therefore may not fully reflect the dynamics of human immunity. We hypothesized that arrays of human monoclonal antibodies (hmAbs) to influenza could be employed in a pattern-recognition approach to expedite IAV serology and to study the antigenic evolution of newly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…Arrayed Imaging Reflectometry (AIR) has been used to provide information about anti-HA antibody titers in sera against different HA subtypes [38]. More recently, it has been used to demonstrate the multiplex capability of antibody arrays for live influenza virus characterization [39]. Here, we use AIR as a high-throughput screening approach to evaluate the cross-reactivity of a panel of recombinant hmAbs cloned from plasmablasts of volunteers vaccinated with different H3N2 strains (A/Perth/16/2009, A/Wisconsin/67/2005, A/Texas/50/ 2012, and A/Uruguay/716/2007) [39] against H3N2 and H3N8 CIVs and antigenically similar (HK68) or distinct (A/Wisconsin/67/2005, WI05) human H3N2 viruses.…”
Section: Protecting Naïve Populationsmentioning
confidence: 99%
“…Arrayed Imaging Reflectometry (AIR) has been used to provide information about anti-HA antibody titers in sera against different HA subtypes [38]. More recently, it has been used to demonstrate the multiplex capability of antibody arrays for live influenza virus characterization [39]. Here, we use AIR as a high-throughput screening approach to evaluate the cross-reactivity of a panel of recombinant hmAbs cloned from plasmablasts of volunteers vaccinated with different H3N2 strains (A/Perth/16/2009, A/Wisconsin/67/2005, A/Texas/50/ 2012, and A/Uruguay/716/2007) [39] against H3N2 and H3N8 CIVs and antigenically similar (HK68) or distinct (A/Wisconsin/67/2005, WI05) human H3N2 viruses.…”
Section: Protecting Naïve Populationsmentioning
confidence: 99%
“…Numbers on the left indicate the size of molecular markers for proteins (in kilodaltons). these technologies could also be used to assess the blocking capacity of NAbs for the treatment of viral infections or to test the efficacy of novel vaccine approaches (35,36,55,78), including universal influenza vaccine studies. In this study, we demonstrated the feasibility of using BIRFLU to evaluate the therapeutic value of antiviral drugs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neutralizing antibodies (NAbs) are the desired immunological outcome for induction of protective immunity after influenza vaccination (53)(54)(55)(56)(57)(58). However, the majority of assays to test for antibody-mediated protection efficacy in virus neutralization assays usually involve secondary methods to detect the presence of the virus.…”
Section: Birflu Reporter Gene Expression Levels Correlate With Dose-dmentioning
confidence: 99%
“…For example, both the H1N1 A/WSN/1933 and H3N2 A/Fujian/411/2002 strains show identical neutralization profiles against the six HA head antibodies and consequently have similar coordinates near (-0.6,1.2) in the HA head map ( Figure S2). While rare antibodies can inhibit both H1N1 and H3N2 viruses (18,20), if an antibody exists that neutralizes these two strains differently, it would split up the locations of these two viruses.…”
Section: Discussionmentioning
confidence: 99%